A field guide to homicide - Cahoon, Lynn (Cahoon, Lynn. Cat Latimer mystery., 2020)
Cat<U+2019>s sweetheart, Seth, is going all out on an outing into the local mountains<U+2014>for the benefit of the writing group Cat<U+2019>s hosting at her Colorado B&B. But when they try to identify some plant and animal life, they find death instead. The body belongs to a man with a gold claim a few miles away. Instead of striking it rich, he<U+2019>s been struck down. To his surprise, Seth recognizes the victim from his military days<U+2014>and up to now believed he<U+2019>d already died during his last tour of duty. Now Cat has to solve this mystery before the killer takes a hike . . .